Analisis Kebutuhan Alat Gali Muat dan Alat Angkut Menggunakan Simulasi Teori Antrian Pada Produksi Overburden di PT. Haswi Kencana Indah Kecamatan Sumay, Kabupaten Tebo Provinsi Jambi - Arie Sefrizni; Tamrin Kasim (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT. Haswi Kencana Indah is a private company engaged in the mining business, especially Coal. In the process of transporting Overburden to disposal, there is a queue of garbage trucks and a long standby time on transport trucks, this can cause the productivity of the equipment to be small so that the Coal production target in September 2018 24,140 tons / month is not achieved. This is caused by the inefficient working time of mechanical devices. The target of this production is not achieved due to a combination of improper tools, road widths and road levels that do not meet the standards, causing the queue or waiting time for transport in front loading. One way to achieve the production target is to analyze the needs of the digging tool and the appropriate transportation equipment. Based on the results of the study, it can be concluded that the productivity of the Doosan 500 LCV excavator is 279.93 tons / hour and the productivity of 5 Mitsubishi Fuso 220 PS dump trucks is 139.57 tons / hour and the productivity of dump trucks has not been able to reach the target of 200 tons / hour. To increase the productivity of mechanical tools can increase the effective time of work and improve the composition of the equipment obtained by the productivity of 1 unit of Doosan 500 lcv excavator 251,14 tons / hour and 4 units of Mitsubishi Fuso 220 PS dump truck transport 287,73 tons / hour. From the results of this study it can be seen that the effective working time and work harmony of actual mechanical devices have not been maximized. Keywords: Queue Method, Work Efficiency, Match Factor, Production, Dump Truck.